2023
DOI: 10.1177/10482911231212936
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Mental Health, and Coping Among Workers in the Northern California Cannabis Industry: A Qualitative Descriptive Analysis

Stella Beckman,
Xóchitl Castañeda,
Likhi Rivas
et al.

Abstract: California is home to a multibillion-dollar cannabis (marijuana) industry, but little is known about the occupational health and safety hazards faced by cannabis workers and even less of the stress, mental health, and coping mechanisms among these workers. Previous research has been based on long-term workers at legal businesses, but most California cannabis is produced and sold unlawfully. There are many seasonal workers whose experiences have not been studied. A qualitative study based on focus group discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The other agricultural product whose production and use is examined in this issue is cannabis. 8 Through qualitative research, Beckman and colleagues 8 identified occupational psychosocial hazards for cannabis workers such as long hours, repetitive tasks, geographic and social isolation, emotional labor, high demand and low control, workplace bullying and workplace violence. They identified some policy anomalies in this industry that make these problems difficult to address.…”
Section: Agricultural Products and Drugsmentioning
confidence: 99%
“…The other agricultural product whose production and use is examined in this issue is cannabis. 8 Through qualitative research, Beckman and colleagues 8 identified occupational psychosocial hazards for cannabis workers such as long hours, repetitive tasks, geographic and social isolation, emotional labor, high demand and low control, workplace bullying and workplace violence. They identified some policy anomalies in this industry that make these problems difficult to address.…”
Section: Agricultural Products and Drugsmentioning
confidence: 99%